Making Label Agricultural Processed Product Packaging - Budiandari, Rahmah Utami; Muezzin, Bangkit (OJS Universitas Muhammadiyah Gresik, 2024)
The label is the part of the product that provides information about the product, according to Tjipton, a label is a part of a product that provides information about the product, a label is part from packaging And can become part sign identifier (tags) Which attached on product. At the same time, Kotler revealed that labels are just a presentation product through picture Which designed in a way effective that is part integral in packaging, labels usually only contain the brand name and information about the product, solution is to create a label design for a product that is visually attractive and attractive according to the characteristics of the product, so packaging can be a factor To increase sales power, the label making process goes through several specific stages so that it is suitable and in accordance with the characteristics of a product so that the product is accepted the wider community, the process of making this label goes through several other stages such as the product tracking.